Prosopis africana (African mesquite) Oil as an Alternative to Antibiotic Feed Additives on Broiler Chickens Diets: Haematology and Serum Biochemical Indices - J. O, Alagbe (Central Asian Journal of Theoretical and Applied Science, 2022)
This experiment was conducted to examine the effect of Prosopis africana (African mesquite) oil as an alternative to antibiotic feed additives on broiler chickens diets: haematology and serum biochemical indices. GC-MS analysis of Prosopis africana oil (PSO) revealed the presence of 21 bioactive chemicals with therapeutic properties. A total of 540 1-day old broiler chicks (Ross 307) were randomly assigned to 6 treatments with six replicates consisting of 15 birds each in a completely randomized design. Treatment 1 (T1) (basal diet + 0 % PSO), treatment 2 (basal diet + 1.5 g/kg neomycin), T3, T4, T5 and T6 were fed basal diet with PSO at 100 mg, 200 mg, 300 mg and 400 mg/kg feed respectively. The experiment lasted for 56 during which fresh water and feed were offered ad libitum. Vaccination was also carried out and all other management practices were strictly observed. Result from the analysis revealed that red blood cell, pack cell volume, haemoglobin concentration, mean corpuscular volume, mean corpuscular heamoglobin, mean corpuscular haemoglobin concentration, white blood cells and its differentials were significantly (P˂0.05) different among the treatments. Feeding broilers with PSO resulted in lower values of heterophils/lymphocytes ratio (P˂0.05). Similarly, all the serum biochemical parameters (albumin, globulin, glucose, cholesterol, ALP, AST and ALT) were significantly (P˂0.05) influenced by the treatments; expect for creatinine, urea, triglycerides, LDL and HDL values that were not significantly (P˃0.05) different among the treatments. It was concluded that PSO could be included up to 400 mg/kg diet of broilers without causing any negative effect on the health status of the animal.